Saddled and spurred eaudiobook - James, Lorelei (Blacktop Cowboys, 2012)
Cattleman Bran Turner is left shorthanded during busy calving season when a bull tramples his hired hand. Rural Wyoming isn't exactly a hotbed of qualified candidates, and the only applicant for the position is the pampered town beauty, Harper Masterson. The curvy cowgirl gets under Bran's skin at every turn, but with no other options, he reluctantly hires her. When sexual sparks ignite, down-on-her-luck Harper convinces Bran that not only is she capable of pulling calves, feeding livestock, and handling backbreaking ranch chores, but she doesn't mind getting down and dirty, either. Harper also discovers the hot-bodied cowboy isn't all work and no horseplay . . . and he's got more than a few tricks up his sleeve. Bran will learn quickly that Harper is no country mouse—and that she might just have what it takes to stick around for the long haul.